Aktivitas Antikanker Ekstrak Daun Aglaia elliptica Blume pada Tikus Betina yang Diinduksi 7,12 dimethylbenz[a] antracene - AGUNG ERU WIBOWO; FRANS D. SUYATNA; WAHONO SUMARYONO; NURYATI CHAIRANI SIREGAR (Fakultas Farmasi Universitas Pancasila, 2011)
Aglaia elliptica Blume is one of plants that contain cyclopenta[b] tetrahydrobenzofuran compound with strong cytotoxic effect on various types of cancer cell lines. The objective of this study is to determine the inhibition effect of ethanol extract of A. elliptica leaves on mammary tumor growth in Sprague Dawley female rats induced by 7.12-dimethylbenz[a]anthracene (DMBA). The study was conducted with induction of 50 female rats with DMBA at a dose of 20 mg/kg orally for 11 times. Twenty-five female rats suffering mammary tumor were divided into 5 groups. Three groups were treated with ethanol extract at a dose of 50, 100 and 200 mg/200 g BW one day after the tumor appeared for 30 days, 1 group as a negative control and 1 group as a positive control (doxorubicin 2 μg/200 g BW). The results showed that the induction of DMBA resulting tumor incidence by 74% and tumor multiplicity of 2 nodules/rat. Histopathological analysis of mammary tumor, suggested that the carcinogenesis has reached the level of ductal carcinoma invasive (DCIV). The administration of ethanol extract at dose of 50, 100 and 200 mg/200 g BW suppressed the growth of mammary tumor volume by 30 %, 33.5% and 37.4%, respectively.